Effects of gravity-induced upper-limb blood pressure changes on wave transmission and arterial radial waveform. Issue 6 (June 2016) - Pucci, Giacomo; Battista, Francesca; Anastasio, Fabio; Sanesi, Leandro; Gavish, Benjamin; Butlin, Mark; Avolio, Alberto; Schillaci, Giuseppe
Abstract : Background: Local blood pressure (BP) changes induced by arm tilting may influence pressure wave transmission and reflection. We investigated the effects of upper-limb tilting on radial augmentation index (rAIx) and related central measures [aortic augmentation index (aAIx)]. Methods: In 45 volunteers (age 49 ± 19 years), supine brachial BP and radial artery waveforms were obtained by applanation tonometry with the dominant arm stretched and gently supported in three different positions: at the heart level, with the BP cuff 15 cm above heart level (approximately +30°), and 15 cm below heart level (−30°). Results: Brachial SBP/DBP was 120/68 ± 17/8 mmHg. Mean arterial pressure changed predictably with arm tilting (99 ± 12 mmHg at −30°, 88 ± 10 mmHg at 0°, 77 ± 11 mmHg at +30°, all P < 0.001). rAIx decreased at −30° (69 ± 22%), and increased at +30° (93 ± 20%) compared with 0° (82 ± 20%, all P less than 0.001). Changes in rAIx (value at +30° minus value at −30°) showed an inverse relationship with age ( r = −0.32, P = 0.03). Heart rate, BP and rAIx did not change in the contralateral arm, which was held at the heart level during the examination. aAIx followed the same pattern as rAIx (123 ± 27% at −30°, 144 ± 33% at +30°, 136 ± 31% at 0°, all P less than 0.001); changes in rAIx and aAIx were strongly related each other ( r = 0.82, P < 0.001). Conclusion: Acute gravitational upper-limb BP changes generate opposite, profound changes in rAIx, and major artifactual changes in aAIx. These findings provide a rationale for recommending to keep the upper limb at the heart level during radial waveform assessment.